Clinicopathological features and prognosis of primary pulmonary rhabdomyosarcoma in middle-aged and elderly patients: a case report and literature review - Jin Xiaoxia; Zheng Guihua; Wang Jiatai; Zhu Xinghua; Chen Xudong; Wei Yingze (Journal of International Medical Research, 2023)
To date, only 34 cases of primary pulmonary rhabdomyosarcoma (PPRMS) in the middle-aged and elderly population have been published. However, analyses of the clinicopathological characteristics and prognosis of PPRMS in this population have not been performed. A 75-year-old man visited our hospital because of abdominal pain and discomfort. His serum lactate dehydrogenase, neuron specific enolase, and progastrin-releasing peptide levels were elevated. Positron emission tomography–computed tomography revealed a lobulated mass of 7.6 × 5.5 cm 2 in the lower lobe of the left lung with abnormally high fluoro-2-deoxy- d -glucose metabolism. Histologically, the tumor cells were small with little cytoplasm, deep nuclear staining, and heavily stained nuclear chromatin. Immunohistochemically, the tumor cells were positive for desmin, MyoD1 myogenin, synaptophysin, and CD56. Cytogenetic analysis for FOXO1A translocation was negative. Finally, the patient was diagnosed with PPRMS. He received combined chemotherapy with vincristine 1 mg, actinomycin 0.4 mg, cyclophosphamide 0.8 mg; however, only one course of chemotherapy was completed, and the patient died 2 months after diagnosis. PPRMS in middle-aged and elderly people is a highly malignant soft tissue tumor with significant clinicopathological characteristics.